Clinical Profiles and CMR Findings of Young Adults and Pediatrics with Acute Myocarditis Following mRNA COVID-19 Vaccination: A Case Series - Roberto Manfredi; Francesco Bianco; Valentina Bucciarelli; Giuseppe Ciliberti; Federico Guerra; Nicolò Schicchi; Marcello Tavio; Emanuela Berton; Francesca Chiara Surace; Massimo Colaneri; Sabina Gallina; Marco Pozzi (Vaccines, 2022)
Messenger RNA (mRNA) coronavirus disease of 2019 (COVID-19) vaccines have been recently associated with acute myocarditis, predominantly in healthy young males. Out of 231,989 vaccines administrated in our region (Marche, Italy), we report a case series of six healthy patients (four males and two females, 16.5 years old (Q1, Q3: 15, 18)) that experienced mRNA-COVID-19-vaccines side effects. All patients were hospitalized due to fever and troponins elevation following the second dose of an mRNA-based COVID-19 vaccine. Cardiovascular magnetic resonance (CMR) was performed 72–96 h after vaccination. All patients were treated with colchicine and ibuprofen. Myocarditis was prevalent in males. It was characterized by myocardial edema and late gadolinium enhancement (LGE) in the lateral wall of the left ventricle (LV). One patient showed sole right ventricular involvement, while the females presented with myopericarditis (myocarditis + pericardial effusion). All patients in our series had preserved LV ejection fraction and remained clinically stable during a relatively short inpatient hospital stay. One case presented with atrial tachycardia. At the follow-up, no significant CMR findings were documented after a three-month medical treatment. According to other recently published case series, our report suggests a possible association between acute myocarditis and myopericarditis with mRNA COVID-19 vaccination in healthy young adults and pediatric patients. Not only males are involved, while some arrhythmic manifestations are possible, such as atrial tachycardia. Conversely, we here highlight the benign nature of such complications and the absence of CMR findings after a three-month medical treatment with colchicine and ibuprofen.